Dynamics and emergence of metachronal waves in the ciliary band of a metazoan larva - Poon, Rebecca N.; Jékely, Gáspár; Wan, Kirsty Y. (Science advances, 2025)
From single cells to humans, ciliary arrays exhibit diverse coordination patterns that are essential to normal physiology. A major open question is how cilia self-organize into metachronal waves, where neighboring cilia beat with the same beat pattern but slightly differing phase. In marine invertebrate larvae, cilia are arranged ornately in arrays or bands, which propagate mesmerizing metachronal waves for swimming motility. Here, we investigate ciliary metachronism in larvae of the annelid Platynereis dumerelii, using whole-body high-speed imaging and physical and biological manipulations. The results reveal an unexpected wave structure featuring strong coupling within multiciliated cells that breaks down across cell boundaries. Using laser ablation to selectively remove parts of the ciliary band, we establish the necessity and sufficiency of ciliary band continuity for wave transmission and the importance of nonreciprocal steric interactions. Taking advantage of neuronally controlled whole-body ciliary arrests, we also reveal the dynamics of wave cessation and reestablishment.